Human lower arm analysis during different eating activities - Hussain, Zakia; Zainul Azlan, Norsinnira (IEEE, 2017)
Human lower arm motion analysis is essential in developing robotic rehabilitation systems for assisting people during eating activities. In this research, human wrist and elbow joints motion is analyzed during five different eating activities and using different cutleries which are the fork and spoon. Xsens Motion Tracker (MTwTM) has been used to capture the orientation data in the form of Euler angles of the wrist and elbow joints while eating various food types. The orientation data trajectories of the wrist and elbow joints have been analyzed and important events identified while eating several food types. Statistical tests like analysis of variance (ANOVA) and t-test have been performed to investigate if the motion of the wrist and elbow is influenced by the type of food and the cutlery used. The ANOVA and t-test results revealed that the motion of the wrist and elbow varies according to various food types and as well as the cutlery used during eating. The wrist joint movements showed more significant variations than the elbow joint while eating various food types and using different cutleries that is, the spoon and fork.